Pertimbangan Hakim Memberikan Izin Poligami: Studi pada Putusan Nomor 0428/Pdt.G/2015 di Pengadilan Agama Jambi - Iis Kartika; Imam Haramein (Jurnal Ilmu Sosial dan Humaniora, 2025)
The principle of Islam is monogamy open marriage, that a husband has only one wife at a time. However in certain circumstances (emergencies), for a man to practice polygamy. If likened to a door, then polygamy is an emergency exit that can only be opened when the situation was an emergency. Polygamy has been stipulated in laws and legislation. Islamic people who want to practice polygamy must obtain prior permission from the Religious Court authorities. If you do not get permission then the marriage has no legal force. Jambi Religious Court in 2015 has been granted a permit polygamy Case No. 0428 / Pdt.G / 2015.PA Jambi. The reasons put forward in the letter of application for a license applicant polygamy is the respondent (wife) can not produce offspring. The reason polygamy filed the applicant has been set explicitly in the legislation.  According to Law No. 1 of 1974 on marriage Article 4, paragraph 2, the reason for the permissibility of polygamy among others: a) the wife can not perform their duties as wives; b) there is a wife disability or illness can not be cured; and c) the wife can not give birth to offspring. Sehiningga subject matter is interesting to study how the consideration of the judge in deciding the license application polygamy case No. 0428 / Pdt.G / 2015.PA Jambi. This study used a qualitative approach to the type of normative-juridical studies, the approach by looking at the question of whether in accordance with the norms of society based on Islamic Hkum and existing legislation.  judge in deciding the case No. 0428 / Pdt.G / 2015.PA Jambi is the wife can not give birth to offspring that reason the applicant in accordance with Law No. 1 of 1974 on marriage Article 4 paragraph 2 (c). Besides the judges also consider, if not given the permission for polygamy, the applicant feared to commit acts prohibited by religion, for example zina.didasarkan to kaedah fiqhiyah that prevents damage precedence over putting welfare. While one goal is to get married in the reconciliation descent. Berdasaikan description above, if a wife can not give birth to offspring or infertile, the court may grant the petition of the husband to remarry or polygamy, with the fulfillment of the terms of alternatives and cumulative.